(untitled) (Indian Journal of Arid Horticulture, 2025)
Indian subcontinent is one of the biodiversity regions in the world. These are three bio diversity hotspots namely Northern Eastern Hill region, North western Himalayan region and Western Ghats ate situated in this region. Apart from these three hotspots, several other regions particularly the semi-arid and arid regions also have rich in diversity of plant and animal. The low and erratic rainfall, high evapo-transpiration, extreme temperature regimes, poor soil conditions of these regions helped to evolve several plant species which can grow well under stressful edaphic and environmental conditions. These perennial plant species have played a major role in the food sustainability and livelihood of these regions. Traditionally most of these species were collected from the forest. The recent awareness about potential of ecologically fragile lands for cultivation of fruit trees has not only opened up scope for providing economic sustainability for the natives, especially small farmers, but also for bringing new areas under fruit production. The underutilized fruit crops such as bordi (Ziziphus rotundifolia), jharber (Z. nummularia), lasoda (Cordia myxa), kair (Capparis decidua), phalsa (Grewia subinaequalis), gangana (Grewia tenax), bael (Aegle marmelos), jamun (Syzygium cuminii), pilu (Salvadora oleoides and S. persica), karonda (Carissa carandas), wood apple (Feronia limonia), mulberry (Morus spp.), manila tamarind (Pithocelobium dulce), etc. are found in these regions. A vast diversity of these species exists in the region. The genetic resources of these fruits are rapidly declining due to climate change, urbanization and change in farming systems. There is need to conserve these genetic resources for their utilization for crop improvement programme and future uses. Several attempts have been made by research organizations to collect, conserve and utilize the genetic resources of these underutilized fruit species. Several promising varieties and lines have been identified for enhancement of production, and productivity of these crops. The status of plant genetic resources of some of the important underutilized fruit species of semi-arid and arid regions have been compiled in the review paper.